Development of a Biosensor for Environmental Monitoring Based on Microalgae Immobilized in Silica Hydrogels - Ferro, Yannis (2012)
A new biosensor was designed for the assessment of aquatic environment quality. Three microalgae were used as toxicity bioindicators: Chlorella vulgaris, Pseudokirchneriella subcapitata and Chlamydomonas reinhardtii. These microalgae were immobilized in alginate and silica hydrogels in a two step procedure. After studying the growth rate of entrapped cells, chlorophyll fluorescence was measured after exposure to (3-(3,4-dichlorophenyl)-1,1-dimethylurea) (DCMU) and various concentrations of the common herbicide atrazine. Microalgae are very sensitive to herbicides and detection of fluorescence enhancement with very good efficiency was realized. The best detection limit was 0.1 μM, obtained with the strain C. reinhardtii after 40 minutes of exposure.